Mathematical Modelling of Allelopathy: IV. Assessment of Contributions of Competition and Allelopathy to Interference by Barley - De Li Liu; Min An; I.R. Johnson; J.V. Lovett (SAGE Publishing, 2005)
One of the main challenges to the research on allelopathy is technically the separation of allelopathic effect from competition, and quantitatively, the assessment of the contribution of each component to overall interference. A simple mathematical model is proposed to calculate the contribution of allelopathy and competition to interference. As an example of applying the quantitative model to interference by barley ( Hordeum vulgare cv. Triumph), the approach used was an addition of allelopathic effect, by an equivalent amount, to the environment of the test plant (white mustard, Sinapis alba ), rather than elimination of competition. Experiments were conducted in glasshouse to determine the magnitude of the contributions of allelopathy and competition to interference by barley. The leachates of living barley roots significantly reduced the total dry weight of white mustard. The model involved the calculation of adjusted densities to an equivalent basis for modelling the contribution of allelopathy and competition to total interference. The results showed that allelopathy contributed 40%, 37% and 43% to interference by barley at 6, 12 and 18 white mustard pot −1 . The consistency in magnitude of the calculated contribution of allelopathic effect by barley across various densities of receiver plant suggested that the adjusted equivalent density is effective and that the model is able to assess the contribution of each component of interference regardless of the density of receiver plant.